Mapping of the State of Sexual Health and HIV Management Services in Thirty Italian Provincial Capitals (European journal of volunteering and community-based projects, 2023)
Despite the growing institutional sensitivity towards the issues of inclusion of LGBTQIA+ people (UNAR, 2022; EC, 2018), research on specific populations and community-based services remains marginal in Italy (Aresi, Cuccì, 2018; Van Der Meulen, Muffels, 2016). The present study, which enlisted the participation of the Arcigay territorial network, partially fills this gap by offering a map detailing the current state of services in the field of sexual health and HIV management.The mapping work was configured as an action research aimed at monitoring healthcare services used by LGBTQIA+ individuals or directed towards them, which allowed for the acquisition, through a judgmental sampling, of data from thirty-one Italian territories[1].Data was collected by the association’s operators throughout the national territory between the second and third quarters of 2022 using public communication channels of services. The survey was conducted through a questionnaire divided into nine collection sheets, each for a service category: HIV centers/clinics; Services for people living with HIV; IST serv. & blood sampling centers; PreP, PEP, Vaccines; Psychological, Chems, SerD/SerT, Prisons; Private Social; Local associations health serv.; Local advocacy.A focus group with operators on the difficulties in obtaining information served to provide an interpretative key to the data.The situation is problematic, with no differences between North and South, but rather between regional capitals and provincial towns. The former typically serves as a point of reference for services that are lacking in provincial structures and is the destination for cases requiring specialized care: a significant problem for emergencies requiring local services, particularly when the regional capital is – as it happens in most cases - far away. Exceptions are the large metropolitan cities (Milan, Rome), with a more widespread and diversified distribution of healthcare facilities.In the last three years cases of discrimination have been reported in 19 of the 31 territories examined.Specific services such as PEP or PrEP are poorly institutionalized, regulated, or completely absent. In some cases they are contrasted or linked to the sensitivity of a single person who allows, provided that he is present and also through informal channels, the activation of such services.Vaccination policies for the MSM people are implemented in a very heterogeneous way across the territory, with excellent services in some areas and significant shortcomings in others. Only in Padua and Livorno reception points are provided by private social entitled to problematic Chemsex.The positive relationship between social actors improves the efficiency of the services provided to the LGBTQIA+ community. The need to institutionalize and extend the work carried out on a national scale was immediately deemed appropriate, not only for the involvement of institutions but also for the benefits brought to the organization of advocacy services dedicated to health.The research was made possible thanks to an unconditional contribution from ViiV Healthcare.[1] Where more than 42% of the national population lives (Istat data as of 1/01/2022)